Cone Beam Computed Tomography Imaging in Dental Implants: A Primer for Clinical Radiologists - Bernaerts, Anja; Barbier, Lieven; Abeloos, Johan; De Backer, Tom; Bosmans, Frederik; Vanhoenacker, Filip M.; Casselman, Jan (Seminars in Musculoskeletal Radiology, 2020)
With the introduction of cone beam computed tomography (CBCT) into dentistry in the 1990s, radiologists have become more frequently involved in dental implant planning. This article describes the information that should be included in a radiology report to achieve a successful implantation. The justification to use CBCT during the preoperative planning phase is based on the need to evaluate patient-specific anatomy in detail (general condition of the jaw, bone quantity, and bone quality), the application of more advanced surgical techniques (maxillary sinus augmentation procedure, zygomatic implants), and the integrated presurgical planning and virtual patient approach. Postoperatively, CBCT is used when implant retrieval is anticipated and two-dimensional radiographs have not provided sufficient information, for evaluation of graft healing, or to assess complications, mostly related to neurovascular trauma.
Keywords: cone beam computed tomography; dental implants; alveolar ridge augmentation; implant failure; imaging